A DEMOGRAPHIC PICTURE ON MEDICAL CHECK UP PATIENTS AND ITS ASSOCIATION WITH PATIENT SATISFACTION LEVEL AT X HOSPITAL IN WEST JAKARTA FOR THE PERIOD OF OCTOBER 2018- FEBRUARY 2019 - Prisca Gisella; Adang Bachtiar (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Nowadays, the trend of non-communicable diseases is increasing around the world. The Sustainable Development Goals (SDG’S) sets the target to decrease number of mortality and morbidity from non-communicable diseases. One of the strategies to achieve the target is by doing medical checkup routine in the hospital. To do medical check-up is affecting by the patient satisfaction with the hospital services. The characteristic of patients can influence the patient to do medical check-up andwill affect the satisfaction level with the hospital services. This study aims to examine the demographic characteristic of patients associated with patient’s satisfaction level in hospital “X”. Methods: This study was a quantitative study used cross-sectional method. The sample in this study was 502 patients during October 2018 to February 2019. The dependent variable in this study was patient’s satisfaction. The independent variables were age, gender, residential area, marital status, and patient status in hospital. The data was analysed in univariate and bivariate analysis used Chi-square. Results: The demographic characteristic of patients in hospital “X” were majority female, had aged 50 years and older, married, lived near hospital “X”, and actually old patient in the hospital. Bivariate analysis showed that age associated with patient’s satisfaction level (p value = 0.000, CI 95%). Meanwhile the other demographic characteristics were not statistically significant with patient’s satisfaction. Conclusion: This study showed that majority of the patients who did medical check-up in the hospital “X” had aged 50 years and older, married, lived near hospital “X”, and actually old patient in the hospital. The aged of the patient was statistically significant associated with patient’s satisfaction. Therefore, the medical check-up service of hospital “X” should be improved based on existing market segment. Keywords: Medical Check Up, demographic characteristic, satisfaction